2017
DOI: 10.3390/jcm6090086
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Dependent Trimethylamine-N-oxide and Serum Biomarkers in Patients with T2DM and Advanced CKD

Abstract: Trimethylamine-N-oxide (TMAO) is a product of dietary, gut microbiome, and tissues metabolism. Elevated blood TMAO levels are associated with heart attack, stroke and chronic kidney disease (CKD). The purpose of our study was to investigate the gut microbiota associated with trimethylamine (TMA) production, the precursor of TMAO, and the serum levels of TMAO and inflammatory biomarkers associated with type 2 diabetes mellitus (T2DM) and CKD. Twenty adults with T2DM and advanced CKD and 20 healthy adults partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 53 publications
3
142
0
5
Order By: Relevance
“…First, Cho CE et al revealed that TMAO production potential is detected in Firmicutes but is absent in Bacteroidetes in healthy volunteers when consuming food rich in TMAO . Furthermore, other report showed that there was a higher TMAO‐producing bacteria ratio and TMAO levels in patients with diabetes mellitus type 2 and chronic kidney disease (T2DM‐CKD) . This present evidence has been proved again that gut microbiota plays an obligatory role for TMAO formation from diet rich in choline and TMAO.…”
Section: Discussionsupporting
confidence: 66%
“…First, Cho CE et al revealed that TMAO production potential is detected in Firmicutes but is absent in Bacteroidetes in healthy volunteers when consuming food rich in TMAO . Furthermore, other report showed that there was a higher TMAO‐producing bacteria ratio and TMAO levels in patients with diabetes mellitus type 2 and chronic kidney disease (T2DM‐CKD) . This present evidence has been proved again that gut microbiota plays an obligatory role for TMAO formation from diet rich in choline and TMAO.…”
Section: Discussionsupporting
confidence: 66%
“…High TMAO production can consequently affect lipids [41] and lead to a 43% higher CAD risk due to the reduction of RCT and alteration in bile acid transport, composition, and pool size [92,93,99]. TMAO is also associated with C-reactive protein (CRP) and endothelial dysfunction in the setting of increased gut permeability and is related to increased serum levels of LPS endotoxin [100]. In addition, it can also lead to calcium release and platelet hyperreactivity [101], which can affect CAD development.…”
Section: Trimethylamine-n-oxide Productionmentioning
confidence: 99%
“…TMA production has been found in 102 genomes covering 36 species, and TMA producers include Firmicutes, Proteobacteria, Actinobacteria, and absent in Bacteroidetes [95]. Firmicutes including Anaerococcus, Clostridium, Desulfitobacterium, Enterococcus, Streptococcus, and Proteobacteria including Dseulfovibrio, Enterobacter, Escherichia, Klebsiella, Proteus, Pseudomonas, Actinobacter, and Citrobacter have been associated with TMA production [100]. One study found that 8 species from Firmicutes and Proteobacteria consumed > 60% of choline for TMA production: Anaerococcus hydrogenalis, Clostridium asparagiforme, C. hathawayi, C. sporogenes, Escherichia fergusonii, Proteus penneri, Providencia rettgeri, and Edwardsiella tarda [103].…”
Section: Trimethylamine-n-oxide Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing recognition of a contributory role of gut microbiota to health and disease promises that great efforts have devoted to define the cause-effect between gut microbiota and preterm birth [6][7][8][9]. Moreover, experimental and clinical studies have demonstration that TMAO synthesized by the intestinal microbiota is involved in the progression of atherosclerosis, cardiovascular disease, type 2 diabetes, vitamin D deficiency, chronic kidney disease, non-alcoholic fatty liver disease [10][11][12]. Those adverse impacts induced by microbial-related metabolite TMAO may directly affect the physical condition of pregnant women and birth outcomes [13,14].…”
mentioning
confidence: 99%